Sustainable distribution practices among chemical firms in Malaysia - Omar, Salmah; Othman, Norfaridatul Akmaliah; Mustafar, Mastora (2018)
The purpose of this paper is to investigate the implementation of sustainable distribution practices by chemical firms in Malaysia to reduce the negative externalities on environment.Sustainable distributions is concerned with producing and distributing goods in a sustainable way, taking account of environmental and social factors.It also refers to a sustainable logistics which suggests compatibility with the environment.Sustainable distribution can have major impact on reducing the environmental burden of the industry especially in terms of greenhouse gases emissions and pollutions.